SOSIALISASI PENGGUNAAN MEDIA SOSIAL YANG BAIK DAN PENGUASAAN LITERSI DIGITAL BAGI MASYARAKAT DESA TEPI LAUT KECAMATAN BENGKULU UTARA - Ade Bayu Saputra; Syafryadin; Dharma Manggala Putra; Muhammad Sobri (Yayasan Pendidikan Islam dan Multikultural, 2023)
Social media has become an integral part of modern life, influencing social interactions, information exchange and the way we participate in digital culture. Digital literacy, on the other hand, refers to a person's ability to critically access, analyze, assess and create digital content. Digital literacy skills are becoming increasingly important along with the development of information and communication technology. This study aims to investigate the role of social media in improving digital literacy among its users. The research method used is a literature review of sources relevant to this topic. The results show that social media has great potential in facilitating digital literacy in various ways. Firstly, social media provides extensive access to information and online learning resources, allowing users to quickly acquire knowledge on various topics. Secondly, interaction in the form of comments, discussions and content sharing on social media platforms can help users develop critical analysis skills of the information they encounter. Third, the ability to participate in online communities encourages creativity and lateral thinking, which are important aspects of digital literacy.